BARRIERS TO IMPLEMENTATION OF EARLY PEANUT INTRODUCTION AMONG PEDIATRICIANS, FAMILY PHYSICIANS, AND ALLERGISTS. (18th May 2018) - Singer, Alexander; Abrams, Elissa; Soller, Lianne; Chan, Edmond
Abstract: BACKGROUND: The approach to peanut allergy prevention has shifted with publication of the Learning Early About Peanut (LEAP) trial and recently released NIAID guideline recommending early peanut introduction in high risk infants. OBJECTIVES: Our objective was to determine whether current practice patterns at both the allergist and primary care level are in keeping with the LEAP recommendations and NIAID guideline. DESIGN/METHODS: A 17-question survey was distributed in 2016 to Canadian allergists through the Canadian Society of Allergy and Clinical Immunology, paediatricians through the Canadian Paediatric Society, and a sample of practicing family physicians. RESULTS: There was variability in the definition of infants at high risk for peanut allergy and recommendations for age of introduction of allergenic solids. There was also variability in how often allergist evaluation was recommended for infants with egg allergy or severe eczema prior to peanut introduction, with allergists 9 times more likely to recommend pre-emptive peanut testing in infants with severe eczema prior to peanut introduction. The majority of family physicians (77.1%), paediatricians (91.4%) and allergists (89.1%) did not believe there was harm to introduction of solids between 4–6 months of age, or that breastfeeding rates would be affected with earlier solid introduction. CONCLUSION: Further education about the implications of LEAP is required. There are broad issues (such as the definition of a high risk infant) that require international consensus. Most primary care physicians and allergists do not believe there are harms to introduction of allergenic solids prior to 6 months of age, or that breastfeeding rates will be affected.